Water-absorbent resin and waterproofing material
A heat-resistant water-absorbing resin with a gel viscosity holding rate of 0.5 or more, achieved through polymerization and crosslinking, addresses the issue of resin decomposition at elevated temperatures, ensuring effective water stop performance.
Patent Information
- Application Number
- JP2021511969
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-29
- Filing Date
- 2020-03-27
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2040-03-27
AI Technical Summary
Conventional water-absorbing resins used in cable water stops lack heat resistance, leading to decomposition and reduced effectiveness at elevated temperatures, limiting their use in various environments.
The development of a water-absorbing resin with a specific gel viscosity holding rate adjusted to a range of 0.5 or more, achieved through polymerization of water-soluble ethylene unsaturated monomers and the use of internal and external crosslinking agents, ensuring high heat resistance even after water absorption.
The resin maintains excellent heat resistance and water absorption capabilities, preventing decomposition and sustaining water stop effectiveness in high-temperature conditions.
Smart Images

Figure 0007625513000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a water-absorbent resin and a water-stopping material. [Background technology]
[0002] It is known that water-absorbent resins have excellent water absorption capacity and can exert a water-stopping effect, and therefore can be applied to various applications requiring water-stopping properties. For example, water-absorbent resins are used as water-stopping materials for communication cables such as optical cables and metal cables, power cables, and the like.
[0003] Patent Document 1 discloses a technology in which a water-blocking material formed by sealing a water-absorbent sheet containing a water-absorbent resin in an exterior material makes it difficult for the gel of the water-absorbent resin that swells after absorbing water to leak out. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-147281 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional water-stopping materials using water-absorbing resins did not have sufficient heat resistance, and therefore, when the water-stopping material absorbs water (i.e., when it becomes gelled), the water-absorbing resin constituting the water-stopping material is likely to decompose when the temperature of the water-stopping material rises due to electric heat or the like, which causes a significant decrease in the water-stopping effect. In particular, cables such as communication cables and power cables are installed in various environments around the world, and if the water-stopping material has low heat resistance, the installation locations of the cables are naturally limited to areas with mild temperatures. It is also known that the conductor of a power cable heats up to about 90°C when it is used. From this perspective, there has been a strong demand for the development of a water-absorbing resin that can be used as a water-stopping material for cables in high-temperature environments.
[0006] The present invention has been made in consideration of the above, and has an object to provide a water-absorbent resin that has excellent heat resistance even when in a water-absorbed state, and a water-stopping material including the water-absorbent resin. [Means for solving the problem]
[0007] As a result of extensive research into achieving the above-mentioned object, the inventors discovered that the above-mentioned object can be achieved by adjusting the retention rate of gel viscosity derived from a specific calculation formula to a specific range, and thus completed the present invention.
[0008] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 The polymer has a crosslinked structure of a water-soluble ethylenically unsaturated monomer. The following formula (I) Gel viscosity retention rate at high temperatures S=B / A (I) (In formula (I), A represents the initial gel viscosity (mPa s), and B represents the gel viscosity (mPa s) after 10 days.) The water-absorbent resin has a gel viscosity retention rate S value of 0.5 or more. Section 2 Item 2. The water-absorbing resin according to item 1, wherein the polymer has a structure crosslinked with a post-crosslinking agent. Section 3 Item 3. A water-stopping material comprising the water-absorbent resin according to item 1 or 2. Effect of the Invention
[0009] The water-absorbent resin according to the present invention has excellent heat resistance even after absorbing water. Furthermore, the water-stopping material according to the present invention contains the water-absorbent resin as a constituent element, and therefore has excellent heat resistance even after absorbing water. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiments of the present invention will be described in detail. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a certain numerical range can be arbitrarily combined with the upper limit or lower limit of another numerical range. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. In addition, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values before and after "~" as the lower limit and upper limit.
[0011] 1.Water absorbent resin The water-absorbing resin of the present invention has a structure in which a polymer of a water-soluble ethylenically unsaturated monomer is crosslinked, and is represented by the following formula (I): Gel viscosity retention rate at high temperatures S=B / A (I) The value of the gel viscosity retention rate S represented by the following formula (I) is 0.5 or more. Here, in formula (I), A indicates the initial gel viscosity (mPa·s), and B indicates the gel viscosity (mPa·s) after 10 days. In particular, A indicates the gel viscosity in a state where the water-absorbent resin is swollen 1000 times with water, and B indicates the gel viscosity after 10 days have passed since the water-absorbent resin swollen 1000 times is heat-treated under predetermined conditions. In the present invention, the method for measuring the gel viscosity retention rate S of the water-absorbent resin is in accordance with the method described in [Method for measuring gel viscosity retention rate] in the Examples section below. In the above formula (I), "at high temperature" means in an environment of 90±2°C.
[0012] The water absorbent resin of the present invention has a gel viscosity retention rate S of 0.5 or more, i.e., the lower limit of the gel viscosity retention rate S is 0.5, so that the water absorbent resin has excellent heat resistance even after absorbing water. In other words, even if the water absorbent resin is placed in a high-temperature environment in a water-absorbed state, decomposition and deterioration of the water absorbent resin are unlikely to occur, so that the water absorbent resin can easily maintain the water-absorbed state even in a high-temperature environment.
[0013] In the water absorbent resin of the present invention, the value of gel viscosity retention rate S is preferably 0.52 or more, more preferably 0.55 or more, and particularly preferably 0.60 or more. In addition, in the water absorbent resin of the present invention, the upper limit of the value of gel viscosity retention rate S is not particularly limited. For example, the value of gel viscosity retention rate S can be 1.5 or less, and more preferably 1.3 or less.
[0014] In the water absorbent resin of the present invention, the initial gel viscosity, that is, the value of A in formula (I) is not particularly limited. For example, the initial gel viscosity of the water absorbent resin can be 4000 mPa·s or more, preferably 4500 mPa·s or more, from the viewpoint that the water absorbent resin is unlikely to decompose even after absorbing water and is likely to have excellent heat resistance. In addition, the upper limit of the initial gel viscosity of the water absorbent resin is not particularly limited. For example, the initial gel viscosity A of the water absorbent resin can be 20000 mPa·s or less, preferably 15000 mPa·s or less, more preferably 13000 mPa·s or less, and even more preferably 9000 mPa·s or less.
[0015] The water-absorbing resin of the present invention has a structure in which a polymer of a water-soluble ethylenically unsaturated monomer (hereinafter, sometimes simply referred to as a polymer) is crosslinked. The polymer may have a structure crosslinked by an internal crosslinking agent described later, or may have a structure crosslinked by a post-crosslinking agent described later instead of or in addition to the internal crosslinking agent. When the polymer has a structure crosslinked by a post-crosslinking agent, the crosslinking density in the vicinity of the surface of the water-absorbing resin becomes high. In addition, by crosslinking the polymer with a post-crosslinking agent, the gel viscosity retention rate S value is easily set to 0.5 or more.
[0016] In the water-absorbing resin of the present invention, when the polymer has a crosslinked structure, the crosslinked structure is formed when the water-soluble ethylenically unsaturated monomer is polymerized. The crosslinking density of the crosslinked structure can be adjusted according to the amount of the crosslinking agent used, which is the same as or different from the above-mentioned post-crosslinking agent, used when the water-soluble unsaturated monomer is polymerized. In this specification, the crosslinking agent used for crosslinking the inside of the polymer is called an internal crosslinking agent to distinguish it from the post-crosslinking agent. Examples of the internal crosslinking agent that can be used will be described in detail in the section "2. Method for producing water-absorbing resin" below.
[0017] As the water-soluble ethylenically unsaturated monomer, for example, known monomers that can be used in general water-absorbing resins can be widely applied. Examples of the water-soluble ethylenically unsaturated monomer include (meth)acrylic acid (in this specification, "acry" and "methacry" are collectively referred to as "(meth)acryl", the same applies below) and its salts; 2-(meth)acrylamido-2-methylpropanesulfonic acid and its salts; nonionic monomers such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, 2-hydroxyethyl(meth)acrylate, N-methylol(meth)acrylamide, and polyethylene glycol mono(meth)acrylate; and amino group-containing unsaturated monomers such as N,N-diethylaminoethyl(meth)acrylate, N,N-diethylaminopropyl(meth)acrylate, and diethylaminopropyl(meth)acrylamide, and their quaternized products. These water-soluble ethylenically unsaturated monomers may be used alone or in combination (copolymerized) of two or more. Among these, (meth)acrylic acid and salts thereof, (meth)acrylamide, and N,N-dimethylacrylamide are preferred from the viewpoint of industrial ease of availability, and (meth)acrylic acid and salts thereof are more preferred.
[0018] When acrylic acid and its salts are used as these water-soluble ethylenically unsaturated monomers, acrylic acid and its salts are used as the main water-soluble ethylenically unsaturated monomers, and it is preferable that they are used in an amount of 70 to 100 mol % based on the total number of moles of the water-soluble ethylenically unsaturated monomers.
[0019] The water-soluble ethylenically unsaturated monomer may be used in the form of an aqueous solution in order to increase the dispersion efficiency in a hydrocarbon dispersion medium when performing reverse phase suspension polymerization described later. The concentration of the monomer in such an aqueous solution is not particularly limited, but is usually 20% by mass or more and not more than the saturated concentration, preferably 25 to 90% by mass, and more preferably 30 to 85% by mass.
[0020] When the water-soluble ethylenically unsaturated monomer has an acid group such as (meth)acrylic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, etc., the acid group may be neutralized in advance with an alkaline neutralizer as necessary. Such alkaline neutralizers are not particularly limited, and examples thereof include alkali metal salts such as sodium hydroxide, sodium carbonate, sodium hydrogen carbonate, potassium hydroxide, and potassium carbonate; ammonia, etc. In particular, these alkaline neutralizers may be used in the form of an aqueous solution in order to simplify the neutralization operation. The above-mentioned alkaline neutralizers may be used alone or in combination of two or more kinds.
[0021] The degree of neutralization of the water-soluble ethylenically unsaturated monomer by the alkaline neutralizing agent is not particularly limited. In order to increase the osmotic pressure of the obtained water absorbent resin to improve the water absorption performance and to prevent problems such as safety caused by the presence of an excess alkaline neutralizing agent, the degree of neutralization of all acid groups of the water-soluble ethylenically unsaturated monomer is usually preferably 10 to 100 mol%, more preferably 30 to 80 mol%.
[0022] In the water absorbent resin of the present invention, as the type of the post-crosslinking agent, for example, a known post-crosslinking agent that can be used for a water absorbent resin can be widely applied. As the post-crosslinking agent, a compound having two or more reactive functional groups can be used. Specific examples of the post-crosslinking agent include polyols such as ethylene glycol, propylene glycol, 1,4-butanediol, trimethylolpropane, glycerin, polyoxyethylene glycol, polyoxypropylene glycol, and polyglycerin; polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, (poly)propylene glycol polyglycidyl ether, and (poly)glycerol polyglycidyl ether; epichlorohydrin, epibromohydrin, α-methylepichlorohydrin, Examples of the epoxy compounds include haloepoxy compounds such as diisocyanate, isocyanate compounds such as 2,4-tolylene diisocyanate and hexamethylene diisocyanate; oxetane compounds such as 3-methyl-3-oxetanemethanol, 3-ethyl-3-oxetanemethanol, 3-butyl-3-oxetanemethanol, 3-methyl-3-oxetaneethanol, 3-ethyl-3-oxetaneethanol and 3-butyl-3-oxetaneethanol; oxazoline compounds such as 1,2-ethylenebisoxazoline; carbonate compounds such as ethylene carbonate; and hydroxyalkylamide compounds such as bis[N,N-di(β-hydroxyethyl)]adipamide. Among these, polyglycidyl compounds such as (poly)ethylene glycol diglycidyl ether, (poly)ethylene glycol triglycidyl ether, (poly)glycerin diglycidyl ether, (poly)glycerin triglycidyl ether, (poly)propylene glycol polyglycidyl ether, (poly)glycerol polyglycidyl ether, etc. are particularly preferred. These post-crosslinking agents may be used alone or in combination of two or more kinds.
[0023] The water absorbent resin of the present invention may contain a chelating agent as necessary. By containing a chelating agent in the water absorbent resin, the gel viscosity retention rate S is likely to be 0.5 or more, and the heat resistance of the water absorbent resin in a water-absorbed state can be further improved.
[0024] The type of the chelating agent is not particularly limited, and for example, known metal chelating agents can be widely used. From the viewpoint of further improving the heat resistance of the water absorbent resin after absorbing water, it is preferable that the chelating agent has 5 or more ligands. The upper limit of the number of ligands that the chelating agent has can be, for example, 12, 11, or 10.
[0025] Specific examples of the chelating agent include ethylenediaminetetraacetic acid, nitrilotriacetic acid, hydroxyethylenediaminetriacetic acid, diethylenetriaminepentaacetic acid, dihydroxyethylglycine, diethylenetriaminepentamethylenephosphonic acid, and salts thereof. When the chelating agent is in the form of a salt, the type of salt is not particularly limited, and examples thereof include alkali metal salts such as sodium and potassium, alkaline earth metal salts such as magnesium and calcium, organic amine salts, and ammonium salts. In the chelating agent, all or a part of the ligand can form a salt. Only one type of chelating agent can be used, or two or more types can be used in combination.
[0026] Of these, the chelating agent preferably used is diethylenetriaminepentaacetic acid and its salts, or diethylenetriaminepentamethylenephosphonic acid and its salts.
[0027] When the water absorbent resin contains a chelating agent, the content of the chelating agent is not particularly limited. For example, from the viewpoint that the gel viscosity retention rate S is likely to be 0.5 or more and the heat resistance of the water absorbent resin in a water-absorbed state is likely to be improved, the content of the chelating agent relative to 100 parts by mass of the water absorbent resin is preferably 0.6 to 2.0 parts by mass, more preferably 0.8 to 1.5 parts by mass.
[0028] When the water absorbent resin contains a chelating agent, the method of incorporating the chelating agent in the water absorbent resin is not particularly limited. A specific method for incorporating the chelating agent in the water absorbent resin will be described in detail in the section "2. Manufacturing method of water absorbent resin" below.
[0029] When the water-absorbent resin contains a chelating agent, the state in which the chelating agent is present is not particularly limited. For example, the chelating agent may be present inside the water-absorbent resin, on the surface of the water-absorbent resin, on the surface and inside of the water-absorbent resin, or independently of the water-absorbent resin.
[0030] The water-retaining capacity of the water-absorbent resin in physiological saline may be 25 g / g or more, 30 g / g or more, or 35 g / g or more, and may be 60 g / g or less, 55 g / g or less, 50 g / g or less, or 45 g / g or less. When the water-retaining capacity is within these ranges, the water-stopping material containing the water-absorbent resin tends to have a large water absorption capacity, and the water-stopping material tends to easily swell quickly and greatly due to water absorption. The water-retaining capacity of the water-absorbent resin in physiological saline is measured by the method described in the examples below.
[0031] The median particle size of the water-absorbent resin of the present invention is, for example, 10 to 800 μm, preferably 30 to 500 μm, more preferably 50 to 300 μm, and further preferably 100 to 200 μm. The water-absorbent resin of the present invention may have various shapes, for example, spherical, pulverized, granular, elliptical, scaly, rod-like, lump-like, and the like.
[0032] The water absorbent resin of the present invention has excellent heat resistance even after absorbing water because the gel viscosity retention rate S is 0.5 or more. Specifically, even if the water absorbent resin of the present invention is exposed to high temperatures while absorbing water, it is unlikely to decompose, and therefore, even if the water absorbent resin is placed in a high-temperature region such as a desert, it is unlikely to decompose, and therefore the water cutoff effect can be maintained for a long period of time.
[0033] Therefore, the water absorbent resin of the present invention is suitable for various applications, and can be widely applied to various fields, for example, industrial materials such as water-stopping materials and dew-preventing agents, agricultural and horticultural materials such as water-retaining agents and soil conditioners, sanitary materials such as paper diapers and sanitary products, etc. In particular, the water absorbent resin of the present invention can maintain the water-stopping effect for a long period even in high-temperature regions, and is therefore suitable for use in water-stopping materials described below.
[0034] 2. Manufacturing method of water-absorbent resin The water-absorbent resin of the present invention can be produced, for example, by a production method including a step of polymerizing a polymer of a water-soluble ethylenically unsaturated monomer (hereinafter, "polymerization step") and a step of removing water from the polymer (hereinafter, "drying step"). Furthermore, in addition to the polymerization step and the drying step, the production method of the water-absorbent resin can include one or more steps selected from the group consisting of a step of adding a chelating agent (hereinafter, "chelating agent addition step") and a step of treating the polymer with a post-crosslinking agent (hereinafter, "post-crosslinking step"), as necessary. Hereinafter, an example of the production method including the polymerization step and the drying step will be described in detail.
[0035] (Polymerization process) The polymerization step is a step of polymerizing a water-soluble ethylenically unsaturated monomer to obtain a polymer. The polymerization method is not particularly limited, and examples thereof include reversed-phase suspension polymerization, aqueous solution polymerization, and emulsion polymerization. In view of the simplicity of the production process and the ease of adjusting the gel viscosity retention rate S to 0.5 or more, it is preferable to adopt reversed-phase suspension polymerization in the polymerization step. The reversed-phase suspension polymerization is, for example, a method in which a monomer that is poorly soluble in a dispersion medium is suspended in the presence of a dispersion stabilizer and polymerized.
[0036] A hydrocarbon dispersion medium can be used as the dispersion medium used in reversed-phase suspension polymerization. Examples of the hydrocarbon dispersion medium include aliphatic hydrocarbons such as n-hexane, n-heptane, n-octane, and ligroin; alicyclic hydrocarbons such as cyclopentane, methylcyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbons such as benzene, toluene, and xylene. Among these dispersion media, n-hexane, n-heptane, and cyclohexane are preferably used because they are industrially easily available, have stable quality, and are inexpensive. These dispersion media may be used alone or in combination of two or more. Examples of the dispersion medium that can be used include Exxsol Heptane (manufactured by ExxonMobil: hydrocarbons of heptane and its isomers) and Nappar6 (manufactured by ExxonMobil: hydrocarbons of cyclohexane and its isomers), which are known as mixed solvents.
[0037] The water-soluble ethylenically unsaturated monomer that can be used in the reversed-phase suspension polymerization is the same as the water-soluble ethylenically unsaturated monomer described in the above section "1. Water-absorbent resin."
[0038] In the reversed-phase suspension polymerization, a thickener can be used as necessary. Examples of the thickener that can be used include hydroxyethyl cellulose, hydroxypropyl cellulose, methyl cellulose, carboxymethyl cellulose, polyacrylic acid, polyacrylic acid (partially) neutralized product, polyethylene glycol, polyacrylamide, polyethyleneimine, dextrin, sodium alginate, polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene oxide.
[0039] As the dispersion stabilizer used in the reversed-phase suspension polymerization, a surfactant may be used, and examples thereof include sucrose fatty acid esters, polyglycerin fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerin fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylaryl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl gluconamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, phosphoric acid esters of polyoxyethylene alkyl ethers, and phosphoric acid esters of polyoxyethylene alkyl allyl ethers. Among these, from the viewpoint of dispersion stability of the monomer, sorbitan fatty acid esters, polyglycerin fatty acid esters, sucrose fatty acid esters, and the like are preferred. These surfactants may be used alone or in combination of two or more.
[0040] The amount of the surfactant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, per 100 parts by mass of the first-stage water-soluble ethylenically unsaturated monomer, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and to obtain a dispersion effect commensurate with the amount used.
[0041] As a dispersion stabilizer, a polymeric dispersant may be used in combination with the surfactant. Examples of polymeric dispersants that can be used include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified EPDM (ethylene-propylene-diene-terpolymer), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, ethyl cellulose, and ethylhydroxyethyl cellulose. Among these, from the viewpoint of dispersion stability of the monomer, preferred are maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, etc. These polymeric dispersants may be used alone or in combination of two or more kinds.
[0042] The amount of the polymeric dispersant used is preferably 0.1 to 30 parts by mass, more preferably 0.3 to 20 parts by mass, per 100 parts by mass of the first-stage water-soluble ethylenically unsaturated monomer, in order to maintain a good dispersion state of the water-soluble ethylenically unsaturated monomer in the hydrocarbon dispersion medium and to obtain a dispersion effect commensurate with the amount used.
[0043] In the polymerization step, for example, known polymerization initiators can be widely used. Examples of radical polymerization initiators include persulfates such as potassium persulfate, ammonium persulfate, and sodium persulfate; peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, di-t-butyl peroxide, t-butyl cumyl peroxide, and hydrogen peroxide; and azo compounds such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(N-phenylamidino)propane] dihydrochloride, 2,2'-azobis[2-(N-allylamidino)propane] dihydrochloride, and 4,4'-azobis(4-cyanovaleric acid). The radical polymerization initiator can also be used in combination with a reducing agent such as sodium sulfite, sodium hydrogen sulfite, ferrous sulfate, or L-ascorbic acid to form a redox polymerization initiator.
[0044] The lower limit of the amount of radical polymerization initiator used in the polymerization step is preferably 0.01 millimoles, more preferably 0.05 millimoles, per 1 mole of the water-soluble ethylenically unsaturated monomer used, from the viewpoint of polymerization stability.The upper limit of the amount of radical polymerization initiator is preferably 20 millimoles, more preferably 10 millimoles, per 1 mole of the water-soluble ethylenically unsaturated monomer used, from the viewpoint of polymerization stability.By using the radical polymerization initiator in this range, the production of the water-absorbing resin becomes easy.
[0045] In the polymerization step, a chain transfer agent can be used as necessary. Examples of the chain transfer agent include hypophosphites, thiols, thiolic acids, secondary alcohols, and amines.
[0046] In the polymerization step, an internal crosslinking agent can be used as necessary, whereby the polymer obtained in the polymerization step can have a structure in which the inside is crosslinked by the internal crosslinking agent. The internal cross-linking agent may be a compound having two or more polymerizable unsaturated groups. A specific example of the internal cross-linking agent is (poly)ethylene glycol (for example, in this specification, "polyethylene glycol" and "ethylene glycol" are collectively referred to as "(poly)ethylene glycol"). the same applies below], di- or tri(meth)acrylic acid esters of polyols such as (poly)propylene glycol, trimethylolpropane, glycerin polyoxyethylene glycol, polyoxypropylene glycol, and (poly)glycerin; unsaturated polyesters obtained by reacting the above-mentioned polyols with unsaturated acids such as maleic acid and fumaric acid; bisacrylamides such as N,N'-methylenebis(meth)acrylamide; di- or tri(meth)acrylic acid esters obtained by reacting polyepoxides with (meth)acrylic acid; di(meth)acrylic acid carbamyl esters obtained by reacting polyisocyanates such as tolylene diisocyanate and hexamethylene diisocyanate with hydroxyethyl (meth)acrylate; allylated starch; allylated cellulose; diallyl phthalate; N,N',N''-triallyl isocyanurate; and divinylbenzene.
[0047] In addition, examples of the internal crosslinking agent include compounds having two or more polymerizable unsaturated groups, such as (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerin diglycidyl ether, and other glycidyl group-containing compounds; (poly)ethylene glycol, (poly)propylene glycol, (poly)glycerin, pentaerythritol, ethylenediamine, polyethyleneimine, and glycidyl (meth)acrylate. Two or more of these internal crosslinking agents may be used in combination. Among these, from the viewpoint of excellent reactivity at low temperatures, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, and (poly)glycerin diglycidyl ether and N,N'-methylenebisacrylamide are preferred.
[0048] When using an internal crosslinking agent, its amount is not particularly limited, and from the viewpoint of ease of production of water absorbent resin, the lower limit of the internal crosslinking agent is preferably 0.0001 mmol, more preferably 0.0005 mmol, even more preferably 0.001 mmol, and particularly preferably 0.01 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used.The upper limit of the amount of the internal crosslinking agent used is preferably 5 mmol, more preferably 0.5 mmol, and even more preferably 0.05 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer used.
[0049] In the polymerization step, the temperature of the polymerization reaction can be appropriately set depending on the type and amount of the radical polymerization initiator used, and can be, for example, 20 to 110° C., and preferably 40 to 90° C. The reaction time can be set, for example, in the range of 0.1 to 4 hours.
[0050] In the reversed-phase suspension polymerization, the polymerization step can be carried out by, for example, adding an aqueous solution containing a water-soluble ethylenically unsaturated monomer, which has been neutralized as necessary, a thickener, a radical polymerization initiator and an internal crosslinking agent to a dispersion medium in which a polymeric dispersion stabilizer has been dissolved, and then adding a surfactant to create a suspended state. The order in which the raw materials are added is not limited to this.
[0051] In the polymerization step, the water-soluble ethylenically unsaturated monomer is polymerized to produce a polymer. For example, in reversed-phase suspension polymerization, a slurry in which the polymer of the water-soluble ethylenically unsaturated monomer is dispersed is obtained. When an internal crosslinking agent is used, the polymer obtained in the polymerization step has a structure crosslinked by the internal crosslinking agent.
[0052] The reverse phase suspension polymerization may be carried out in one stage or in two or more stages.
[0053] When performing two or more stages of reversed phase suspension polymerization, the first stage of reversed phase suspension polymerization is performed by the above-mentioned method, and then the water-soluble ethylenically unsaturated monomer is added and mixed into the reaction mixture obtained in the first stage polymerization step, and the second and subsequent stages of reversed phase suspension polymerization are performed by the same method as the first stage. In the reversed phase suspension polymerization in each stage from the second stage onwards, in addition to the water-soluble ethylenically unsaturated monomer, a radical polymerization initiator and an internal crosslinking agent added as necessary are added within the range of the molar ratio of each component to the water-soluble ethylenically unsaturated monomer described above, based on the amount of the water-soluble ethylenically unsaturated monomer added during the reversed phase suspension polymerization in each stage from the second stage onwards, and the reversed phase suspension polymerization is performed under the same conditions as the above-mentioned method.
[0054] In addition, in the case where the reversed-phase suspension polymerization is carried out in multiple stages, from the viewpoint of facilitating production of a desired water absorbent resin, it is preferable that the total amount of the polymerization initiator and the total amount of the internal crosslinking agent used as necessary are each set within the above-mentioned range per 1 mole of the water-soluble ethylenically unsaturated monomer used in the reversed-phase suspension polymerization.
[0055] (drying process) The drying step is a step of removing water from the polymer obtained in the polymerization step or the polymer crosslinked with an internal crosslinking agent by applying energy such as heat from the outside to the polymer. For example, in the case of reversed-phase suspension polymerization, in the drying step, the polymer (hydrous gel) obtained in the polymerization step is dispersed in a hydrocarbon dispersion medium and azeotropic distillation is performed to remove water, a hydrocarbon dispersion medium, and the like from the polymer. The drying step may be performed under normal pressure or reduced pressure, and may be performed under a stream of nitrogen or the like to increase the drying efficiency. When the drying step is performed under normal pressure, the drying temperature is preferably 70 to 250°C, more preferably 80 to 180°C, further preferably 80 to 140°C, and particularly preferably 90 to 130°C. When the drying step is performed under reduced pressure, the drying temperature is preferably 40 to 160°C, more preferably 50 to 120°C.
[0056] By carrying out the drying step, the water content of the polymer or the polymer crosslinked with the internal crosslinking agent can be adjusted. The drying step may be carried out simultaneously with the post-crosslinking step described later.
[0057] (Post-crosslinking process) The post-crosslinking step is a step in which the polymer obtained in the polymerization step (including the polymer crosslinked with an internal crosslinking agent) is treated with a post-crosslinking agent. Examples of the type of post-crosslinking agent include the same types as those described in the above section "1. Water-absorbent resin."
[0058] As a method for treating a polymer with a post-crosslinking agent, for example, a post-crosslinking agent and a solvent are mixed to prepare a treatment liquid containing the post-crosslinking agent, and the treatment liquid is brought into contact with the polymer, thereby treating the polymer with the post-crosslinking agent.
[0059] The solvent for preparing the treatment liquid containing the post-crosslinking agent is not particularly limited, and for example, a hydrophilic organic solvent having excellent solubility of the post-crosslinking agent can be used. Examples of the solvent include water, lower alcohols such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, and propylene glycol; ketones such as acetone and methyl ethyl ketone; ethers such as diethyl ether, dioxane, and tetrahydrofuran; amides such as N,N-dimethylformamide; and sulfoxides such as dimethyl sulfoxide. These hydrophilic organic solvents may be used alone, or two or more of them may be used in combination, or they may be used as a mixed solvent with water.
[0060] The treatment liquid can be prepared, for example, by dissolving a post-crosslinking agent in a solvent. The mixing ratio of the post-crosslinking agent to the solvent is not particularly limited, and for example, the post-crosslinking agent can be 0.1 to 10 parts by mass per 100 parts by mass of the solvent.
[0061] The contact of the polymer with the treatment liquid can be carried out, for example, by mixing the polymer with the treatment liquid by an appropriate method. For example, a method can be adopted in which the treatment liquid is added to the polymer while stirring the polymer as it is in a container or in the above-mentioned hydrocarbon dispersion medium.
[0062] From the viewpoint of easily adjusting the gel viscosity retention rate S to 0.5 or more, the lower limit of the amount of the post-crosslinking agent used is preferably 0.01 mmol, more preferably 0.05 mmol, and even more preferably 0.1 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer constituting the post-crosslinked polymer, and the upper limit is preferably 10 mmol, more preferably 5 mmol, and even more preferably 2 mmol, relative to 1 mol of the water-soluble ethylenically unsaturated monomer.
[0063] The reaction temperature in the post-crosslinking step (i.e., the temperature at which the polymer is treated with the post-crosslinking agent) is preferably 50 to 250° C., more preferably 60 to 180° C., and even more preferably 60 to 140° C. The reaction time of the post-crosslinking (i.e., the time at which the polymer is treated with the post-crosslinking agent at the reaction temperature) cannot be determined in general because it varies depending on the reaction temperature, the type and amount of the post-crosslinking agent used, etc., but is usually 1 to 300 minutes, and preferably 5 to 200 minutes.
[0064] The post-crosslinking step is preferably carried out simultaneously with or after the drying step.
[0065] (Chelating agent addition process) The chelating agent addition step is a step for incorporating a chelating agent into the water-absorbent resin. Examples of the type of the chelating agent include the same types as those described in the above section "1. Water-absorbent resin."
[0066] The chelating agent addition step can be carried out, for example, after the drying step, or the chelating agent addition step can be carried out during the polymerization step. When the chelating agent addition step is carried out during the polymerization step, the chelating agent may be added to the container in which the polymerization reaction is carried out before the polymerization reaction proceeds, may be added to the container in which the polymerization reaction is carried out during the polymerization reaction, or may be added after the polymerization reaction is completed. By adding the chelating agent after the polymerization reaction is completed, the above-mentioned embodiment in which the chelating agent is present inside the water-absorbing resin can be realized, and by adding the chelating agent during the polymerization reaction, the above-mentioned embodiment in which the chelating agent is present on the surface and inside the water-absorbing resin can be realized.
[0067] In addition, in the case where the manufacturing method of the water absorbent resin includes the post-crosslinking step, the chelating agent addition step may be performed after the drying step and before the post-crosslinking step, or may be performed after the post-crosslinking step.
[0068] When adding the chelating agent, the chelating agent can be added in a state of solution dissolved in a solvent such as water, or can be added in a solid state without using a solvent. The polymer to which the chelating agent is added may be in a state of dispersion in a dispersion medium, or may be in a state of powder or the like from which the dispersion medium has been removed. When the polymer is in a powder state, the so-called dry blending method can be adopted in the chelating agent addition step.
[0069] In the chelating agent addition step, the amount of the chelating agent used is not particularly limited. For example, from the viewpoint that the gel viscosity retention rate S is likely to be 0.5 or more and the heat resistance of the water absorbent resin in the water-absorbed state is likely to be improved, the chelating agent is preferably added so that the content of the chelating agent is 0.6 to 2.0 parts by mass relative to 100 parts by mass of the finally obtained water absorbent resin, and more preferably 0.8 to 1.5 parts by mass of the chelating agent is added.
[0070] As described above, the water-absorbing resin of the present invention can be produced by a production method including a polymerization step and a drying step, and if necessary, a chelating agent addition step and / or a post-crosslinking step.
[0071] After the polymerization step, additives may be added according to the purpose in order to impart various properties to the obtained water absorbent resin. Examples of such additives include various additives that have been conventionally added to water absorbent resins, such as inorganic powders, surfactants, oxidizing agents, reducing agents, radical chain inhibitors, antioxidants, antibacterial agents, and deodorants.
[0072] 3.Water-stopping materials The water-stopping material of the present invention is not particularly limited in its configuration as long as it includes a water-absorbent resin, and may have, for example, the same configuration as known water-stopping materials. The water-stopping material may be formed from a water-absorbent resin alone. Alternatively, the water-stopping material may be formed by molding a mixture of the water-absorbent resin and rubber and / or a thermoplastic resin or the like. The water-stopping material may also be formed by holding the water-absorbent resin on a nonwoven fabric or paper.
[0073] The water-stopping material of the present invention can be used for various purposes, for example, it can be used in various cables such as communication cables such as optical cables and metal cables, and power cables, and can be particularly suitably used in electric wire cables used underground and under the sea, and optical fiber cables used underground and under the sea. EXAMPLES
[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples. [Example 1] A round-bottomed cylindrical separable flask (hereinafter referred to as round-bottomed flask) with an inner diameter of 100 mm and equipped with a reflux condenser, a dropping funnel, a nitrogen gas inlet tube, and a stirring blade (coated with a fluororesin) having two stages of four inclined paddle blades with a blade diameter of 50 mm was prepared. 700 mL of n-heptane was added to the round-bottomed flask as a petroleum-based hydrocarbon dispersion medium, and 1.10 g of sorbitan monolaurate (manufactured by NOF Corporation, trade name Nonion LP-20R; HLB 8.6) was added as a surfactant, and the temperature was raised to 45°C to prepare an n-heptane solution of the surfactant.
[0075] On the other hand, 92g (1.03 mol) of 80.5% by mass acrylic acid aqueous solution was added to a 300mL beaker as a water-soluble ethylenically unsaturated monomer aqueous solution. While cooling the acrylic acid aqueous solution with ice water, 147.7g of 20.9% by mass sodium hydroxide aqueous solution was dropped into the beaker to neutralize 75 mol% of the acrylic acid. Then, 0.10g (0.00037 mol) of potassium persulfate was added and dissolved as a radical polymerization initiator to prepare an aqueous solution.
[0076] Next, the entire amount of the aqueous liquid was added to the n-heptane solution of the surfactant in a round-bottom flask, and the inside of the round-bottom flask was replaced with nitrogen for 30 minutes while stirring at a stirrer speed of 700 rpm. After this, the round-bottom flask was immersed in a water bath at 70°C to raise the temperature inside the system, and a polymerization reaction was carried out for 1 hour to carry out a polymerization step. By this polymerization step, a hydrous gel polymer was obtained in the round-bottom flask. Next, the round-bottom flask was immersed in an oil bath at 120°C to azeotrope water and n-heptane, and 111.7 g of water was extracted from the system while refluxing n-heptane, to carry out a drying step.
[0077] After this drying step, 2.04 g (0.0018 mol) of a 45% by mass aqueous solution of diethylenetriaminepentaacetic acid·pentasodium salt as a chelating agent having a ligand number of 5 was added to the round-bottom flask, and a chelating agent addition step was carried out.
[0078] After this chelating agent addition step, 4.14g (0.00048 moles) of 2% by mass ethylene glycol diglycidyl ether aqueous solution was added to the round-bottom flask as a post-crosslinking agent.Then, the round-bottom flask was heated to a treatment temperature of 80°C with the post-crosslinking agent, and the post-crosslinking step was carried out by maintaining the temperature for 2 hours.Then, the round-bottom flask was heated to 120°C, and the n-heptane in the round-bottom flask was evaporated at 120°C to obtain 89.2g of granular water-absorbent resin particles.
[0079] [Example 2] 89.2 g of granular water absorbent resin particles was obtained in the same manner as in Example 1, except that 2.04 g (0.0020 mol) of a 45 mass % aqueous solution of diethylenetriaminepentaacetic acid trisodium salt was used as a chelating agent instead of the 45 mass % aqueous solution of diethylenetriaminepentaacetic acid pentasodium salt.
[0080] [Example 3] In Example 1, after the drying step, the post-crosslinking step was carried out without carrying out the chelating agent addition step, and after the post-crosslinking step, the round-bottom flask was heated to 120° C., and n-heptane in the round-bottom flask was evaporated at 120° C. to obtain a polymer having a structure crosslinked with a post-crosslinking agent. Next, 1.0 part by mass of diethylenetriaminepentaacetic acid as a chelating agent was dry-blended with 100 parts by mass of this polymer to obtain a water-absorbent resin.
[0081] [Example 4] 89.2 g of granular water absorbent resin particles was obtained in the same manner as in Example 1, except that 2.97 g (0.0013 mol) of a 31 mass % aqueous solution of diethylenetriaminepentamethylenephosphonic acid-heptasodium salt having a ligand number of 10 was used as a chelating agent instead of the 45 mass % aqueous solution of diethylenetriaminepentaacetic acid-pentasodium salt.
[0082] [Comparative Example 1] Granular water-absorbent resin particles were obtained in the same manner as in Example 3, except that 1.0 part by mass of tetrasodium ethylenediaminetetraacetic acid was used instead of diethylenetriaminepentaacetic acid as a chelating agent.
[0083] [Comparative Example 2] Granular water-absorbent resin particles were obtained in the same manner as in Example 3, except that 1.0 part by mass of ethylenediaminetetraacetic acid was used as the chelating agent instead of diethylenetriaminepentaacetic acid.
[0084] [Method for measuring gel viscosity retention rate] The gel viscosity retention rate was measured by the following method using the water-absorbent resin obtained in each Example and Comparative Example. First, 1500 g of distilled water was added to a 2 L beaker, and a magnetic stirrer bar (13 mmφ×43 mm without ring) was used to stir at 600 rpm. 1.5 g of water-absorbent resin was added to the vortex generated by this stirring, and then stirred for 1 hour. Then, the mixture was filtered through a 200 mesh wire net and allowed to stand for 15 minutes. The gel viscosity of the swollen gel thus obtained was immediately measured and taken as the "initial gel viscosity" (this is defined as the "initial gel viscosity" in the present invention). After this measurement, 250 g of the swollen gel was immediately placed in a 250 mL glass heat-resistant bottle with an outer diameter of 70 mm, and allowed to stand in a hot air dryer (FV-320, manufactured by ADVANTEC) at 90±2°C. The viscosity of the swollen gel was measured every 24 hours (every day). The gel viscosity value after 10 days (defined as "gel viscosity after 10 days" in this invention) was used to calculate the gel viscosity retention rate S according to the following formula (I). Gel viscosity retention rate S=B / A (I) (In formula (I), A represents the initial gel viscosity (mPa s), and B represents the gel viscosity (mPa s) after 10 days.) The gel viscosity was measured using a Vismetron (Shibaura Systems VS-H1 model, rotor No. 5, rotation speed 20 rpm) by adjusting the temperature of the swollen gel to 25±0.5° C. The gel viscosity was measured in a 200 mL glass beaker with an inner diameter of 64 mm and a height of 65 mm.
[0085] [Method of measuring water retention] A cotton bag (Membrane Broad No. 60, 100 mm wide x 200 mm long) containing 2.0 g of absorbent resin was placed in a 500 mL beaker. 500 g of 0.9% by mass sodium chloride aqueous solution (physiological saline) was poured into the cotton bag containing the absorbent resin at once so as not to cause any lumps. The top of the cotton bag was tied with a rubber band, and the cotton bag was left to stand for 30 minutes to allow the absorbent resin to swell. After 30 minutes, the cotton bag was dehydrated for 1 minute using a dehydrator (manufactured by Kokusan Co., Ltd., product number: H-122) set to a centrifugal force of 167 G, and the mass Wa (g) of the cotton bag containing the swollen gel after dehydration was measured. The same operation was performed without adding the absorbent resin, and the empty mass Wb (g) of the cotton bag when wet was measured, and the water retention was calculated from the following formula. Water retention amount (g / g)=[Wa-Wb] / 2.0
[0086] [Method of measuring median particle size] The median particle size of the water-absorbent resin was measured by the following procedure. That is, JIS standard sieves were combined in the following order from the top: a sieve with an opening of 850 μm, a sieve with an opening of 500 μm, a sieve with an opening of 250 μm, a sieve with an opening of 180 μm, a sieve with an opening of 150 μm, a sieve with an opening of 106 μm, a sieve with an opening of 75 μm, and a tray. 50 g of water-absorbent resin was placed on the top sieve of the combination, and classified according to JIS Z 8815 (1994) using a Rotap type shaker (manufactured by Iida Seisakusho Co., Ltd.). After classification, the mass of the particles remaining on each sieve was calculated as a mass percentage relative to the total amount to obtain the particle size distribution. The particle size distribution was calculated by accumulating the particles remaining on the sieves in descending order of particle size, and the relationship between the sieve opening and the accumulated mass percentage of the particles remaining on the sieve was plotted on a logarithmic probability paper. The particle size corresponding to an accumulated mass percentage of 50% by mass was obtained as the median particle size by connecting the plots on the probability paper with a straight line.
[0087] [Table 1]
[0088] Table 1 shows the initial gel viscosity A value, the gel viscosity B value after 10 days, and the gel viscosity retention rate S value of the water-absorbent resin obtained in each of the Examples and Comparative Examples.
[0089] It is seen from Table 1 that the gel viscosity retention rate S of the water absorbent resins obtained in Examples 1 to 4 exceeds 0.5. The number of days required for the gel viscosity A to fall below half of the initial gel viscosity A value was 17 days (2810 mPa s) for the water absorbent resin obtained in Example 1, 18 days (2510 mPa s) for the water absorbent resin obtained in Example 2, 17 days (2480 mPa s) for the water absorbent resin obtained in Example 3, and 11 days (2100 mPa s) for the water absorbent resin obtained in Example 4.
[0090] In contrast, in the water absorbent resins obtained in Comparative Examples 1 and 2, the gel state could not be maintained after 10 days due to decomposition and deterioration. In Comparative Example 1, the gel viscosity after 4 days was 2020 mPa s, and in Comparative Example 2, the gel viscosity after 4 days was 2380 mPa s. In other words, the number of days required for the gel viscosity to fall below half of the initial gel viscosity A was 4 days for both the water absorbent resins obtained in Comparative Examples 1 and 2, and the heat resistance was significantly poor.
[0091] From the above results, it is shown that the water-absorbing resins obtained in Examples 1 to 4 have excellent heat resistance even when they absorb water, and can maintain their water-stopping effect for a long period of time even in a high-temperature environment.
Claims
1. The polymer has a structure in which a water-soluble ethylenically unsaturated monomer polymer is crosslinked with a post-crosslinking agent, Contains a chelating agent having 5 or more ligands, The median particle size is 50 to 300 μm, The following formula (I) Gel viscosity retention rate at 90±2° C. S=B / A (I) (In formula (I), A represents the initial gel viscosity (mPa·s), and B represents the gel viscosity (mPa·s) after 10 days.) The gel viscosity retention rate S represented by is 0.5 or more, A water-absorbent resin having an initial gel viscosity of 4000 mPa·s or more.
2. A water-stopping material comprising the water-absorbent resin according to claim 1.
Citation Information
Patent Citations
Water-absorptive resin composition of excellent stability
JP1989210463A
Hydrophilic polymer and preparation thereof
JP1989279905A
Manufacturing method of water-absorbable resin
JP2003206305A
Aqueous liquid absorbent and its production method
JP2007529295A
Aqueous liquid absorbent and method for producing the same
JP2009509723A